Rodzina jako komunia życia i miłości w Domowym Kościele Ruchu Światło–Życie - Biela, Bogdan (Studia Pastoralne, 2009)
Family in itself is the fulfilment of one of the most basic human needs, since a man in his ontological dimension is homo familiaris. It may serve its purpose due to the fact that it is a privileged place of realization of human love and at the same time a place opened to receiving life. Thanks to this family is able to fulfil the need of an emotional bond with one’s neighbours, mutual understanding, security, a desire to have children as well as religious needs, including initiation into mysteries of religious and ecclesial life. In order to meet these aims a family must become „a community of life and love” (KDK 48). The foundation of this community is a communion of spouses with God which in turn will manifest itself in communion between spouses and communion between parents and their children. This personal vision of marriage and a Christian family, based on the idea of father Franciszek Blachnicki, is the aim of the Home Church. For families participating in the movement a nuptial communion is the foundation of communion of the whole family, and from even broader perspective, an opportunity to build an ecclesial community. This is why a family can and should call itself a home Church. In view of the above the basic aspect of the charism of the Home Church was described as „the self-gift in a marriage and a family”. The basis of formation of a marriage and a family is a nuptial spirituality, which is aspiring to holiness together with one’s spouse. The nuptial communion is built through the so called obligations. They are as follows: daily private prayer, daily family prayer, monthly nuptial dialogue, the rule of life and participation, at least once a year, in a formation retreat. Thanks to implementation of these tasks spouses get closer to one another and to God. The obligations are met by a daily effort of spouses and mutual support of other married couples gathered in the circles of the Home Church.